Multi-Loop Radio Frequency Coil Elements for Magnetic Resonance Imaging: Theory, Simulation, and Experimental Investigation - Frass-Kriegl, Roberta; Hosseinnezhadian, Sajad; Poirier-Quinot, Marie; Laistler, Elmar; Ginefri, Jean-Christophe (Frontiers in Physics, 2020)
Magnetic resonance imaging (MRI) is a major imaging modality, giving access to anatomical and functional information with high diagnostic value. To achieve high-quality images, optimization of the radio-frequency coil that detects the MR signal is of utmost importance. A widely applied strategy is to use arrays of small coils in parallel on MR scanners equipped with multiple receive channels that achieve high local detection sensitivity over an extended lateral coverage while allowing for accelerated acquisition and SNR optimization by proper signal weighting of the channels. However, the development of high-density coil arrays gives rise to several challenges due to the increased complexity with respect to mutual decoupling as well as electronic circuitry required for coil interfacing. In this work, we investigate a novel single-element coil design composed of small loops in series, referred to as “multi-loop coil (MLC)”. The MLC concept exploits the high sensitivity of small coils while reducing sample induced noise together with an extended field of view, similar to arrays. The expected sensitivity improvement using the MLC principle is first roughly estimated using analytical formulae. The proof of concept is then established through fullwave 3D electromagnetic simulations and validated by B1 mapping in MR experiments on phantom. Investigations were performed using two MLCs, each composed of 19 loops, targeting MRI at high (3 T) and at ultra-high field strength (7 T). The 3 T and 7 T MLCs have an overall diameter of 12 cm and 6 cm, respectively. For all investigated MLCs, we demonstrate a sensitivity improvement as compared to single loop coils. For small distances inside the sample, i.e. close to the coil, a sensitivity gain by a factor between 2 and 4 was obtained experimentally depending on the set-up. Further away inside the sample, the performance of MLCs is comparable to single loop coils. The MLC principle brings additional degrees of freedom for coil design and sensitivity optimization and appears advantageous for the development of single coils but also individual elements of arrays, especially for applications with a larger area and shallow target depth, such as skin imaging or high-resolution MRI of brain slices.